The Origin and 3D Architecture of a Km-Scale Deep-Water Scour-Fill: Example From the Skoorsteenberg Fm, Karoo Basin, South Africa - Hansen, L. A. S.; Healy, R. S.; Gomis-Cartesio, L.; Lee, D. R.; Hodgson, D. M.; Pontén, A.; Wild, R. J. (Frontiers in Earth Science, 2021)
Scours, and scour fields, are common features on the modern seafloor of deep-marine systems, particularly downstream of submarine channels, and in channel-lobe-transition-zones. High-resolution images of the seafloor have improved the documentation of the large scale, coalescence, and distribution of these scours in deep-marine systems. However, their scale and high aspect ratio mean they can be challenging to identify in outcrop. Here, we document a large-scale, composite erosion surface from the exhumed deep-marine stratigraphy of Unit 5 from the Permian Karoo Basin succession in South Africa, which is interpreted to be present at the end of a submarine channel. This study utilizes 24 sedimentary logs, 2 cored boreholes, and extensive palaeocurrent and thickness data across a 126 km2 study area. Sedimentary facies analysis, thickness variations and correlation panels allowed identification of a lower heterolithic-dominated part (up to 70 m thick) and an upper sandstone-dominated part (10-40 m thick) separated by an extensive erosion surface. The lower part comprises heterolithics with abundant current and sinusoidal ripples, which due to palaeocurrents, thickness trends and adjacent depositional environments is interpreted as the aggradational lobe complex fringes. The base of the upper part comprises 2-3 medium-bedded sandstone beds interpreted as precursor lobes cut by a 3-4 km wide, 1-2 km long, and up to 28 m deep, high aspect ratio (1:100) composite scour surface. The abrupt change from heterolithics to thick-bedded sandstones marks the establishment of a new sediment delivery system, which may have been triggered by an updip channel avulsion. The composite scour and subsequent sandstone fill support a change from erosion- and bypass-dominated flows to depositional flows, which might reflect increasingly sand-rich flows as a new sediment route matured. This study provides a unique outcrop example with 3D stratigraphic control of the record of a new sediment conduit, and development and fill of a large-scale composite scour surface at a channel mouth transition zone, providing a rare insight into how scours imaged on seafloor data can be filled and preserved in the rock record.